أثر التدريب في تنمية المسار الوظيفي للعاملين دراسة ميدانية على العاملين في مديرية مالية حمص - الحمصي دانيال طالب (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تتناول هذه الدراسة العلاقة بين التدريب وتنمية المسار الوظيفي للعاملين في مديرية مالية حمص, إذ تلخصت مشكلة الدراسة في عدد من التساؤلات حول مدى إدراك العاملين لمفهوم المسار الوظيفي وهل تراعي البرامج التدريبية في المديرية متطلبات تنمية المسار الوظيفي, وقد تمثلت أهداف الدراسة في التعرف على مستوى التدريب الموجود في المديرية وعلى دوره في تعزيز وتدعيم عملية تنمية المسار الوظيفي , بالإضافة إلى التعرف على العلاقة بين بعدي تنمية المسار الوظيفي (تخطيط المسار وإدارة المسار), وتم جمع بيانات الدراسة من خلال استبيان يحتوي على مجموعة من الأسئلة عن متغيرات الدراسة , حيث وزع على عينة عشوائية بلغت (150) من العاملين في مختلف الدوائر والأقسام في المديرية تم استرداد (132) استمارة واستبعاد (9) استمارات لنقص في المعلومات , أي أن الاستمارات الجاهزة للتحليل بلغت (123) استمارة, وكان من أهم النتائج أن مستوى التدريب في المديرية كان متوسطاً ووجود تأثير معنوي للتدريب في تنمية المسار الوظيفي ,حيث كانت العلاقة بين التدريب وتنمية المسار الوظيفي ببعديه( البعد الفردي والبعد التنظيمي ) متوسطة وموجبة , بالإضافة إلى وجود إرتباط معنوي بين تخطيط المسار وإدارة المسار. This study examines the relationship between training and career development for workers in the financial directorate of Homs. The problem of study summarized in a number of questions about the perceptions of workers to the concept of career development. Do the training programs consider the requirements of career development in the Directorate? This study aimed to identtify the level of training in the directorate and its role in enhancing and strengthening the process of career development, as well as to identify the relationship between the two dimensions of career development (career planning and career management). The data of study were collected through a questionnaire contains a set of questions about the variables of the study, and distributed to a random sample of (150) workers in various departments and sections of the Directorate. The number of forms which recovered was (132) forms and excluded (9) forms due to a lack of information. The forms which were ready for analysis amounted to (123) forms. The most important results are: the level of training in the Directorate was medial, recognising the significant effect of training in the career development, and the relationship between training and career development with its two dimensions (individual and organizational dimension) was medial and positive, and the existence of a significant correlation between career planning and career management.